2020
DOI: 10.1084/jem.20200885
|View full text |Cite
|
Sign up to set email alerts
|

ZBP1: A STARGᐰTE to decode the biology of Z-nucleic acids in disease

Abstract: ZBP1 triggers NLRP3 inflammasome activation/pyroptosis, apoptosis, and necroptosis; the specific ligand for ZBP1 activation remains ambiguous. Recent studies, including Devos et al. in this issue of JEM (https://doi.org/10.1084/jem.20191913), collectively suggest that ZBP1 sensing Z-nucleic acids is critical for cell death/inflammatory disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 19 publications
0
33
0
Order By: Relevance
“…74 These data suggest that ZBP1 can directly sense endogenous transcripts during development to induce programmed cell death and inflammation. 63 Interestingly, while around 85% of Zbp1 -/-Ripk1 E-KO and Zbp1 mR1/mR1 Ripk1 E-KO mice remain healthy for more than 40 weeks, approximately 75% of the Zbp1 mZα2/mZα2 Ripk1 E-KO mice develop mild skin inflammation at the age of 40 weeks, suggesting that ZBP1 may function as a adapter protein downstream of some factors. 74 In addition to its functions in infection and organismal development, ZBP1 is also involved in inflammatory bowel diseases (IBD).…”
Section: Role Of Zbp1 In Development and Inflammatory Bowel Diseasementioning
confidence: 99%
See 3 more Smart Citations
“…74 These data suggest that ZBP1 can directly sense endogenous transcripts during development to induce programmed cell death and inflammation. 63 Interestingly, while around 85% of Zbp1 -/-Ripk1 E-KO and Zbp1 mR1/mR1 Ripk1 E-KO mice remain healthy for more than 40 weeks, approximately 75% of the Zbp1 mZα2/mZα2 Ripk1 E-KO mice develop mild skin inflammation at the age of 40 weeks, suggesting that ZBP1 may function as a adapter protein downstream of some factors. 74 In addition to its functions in infection and organismal development, ZBP1 is also involved in inflammatory bowel diseases (IBD).…”
Section: Role Of Zbp1 In Development and Inflammatory Bowel Diseasementioning
confidence: 99%
“…61 Later, however, it was demonstrated that loss of ZBP1 has no effect on DNA-induced immune responses. 62,63…”
Section: Zb P1 S En S E S Z-rna Produced By Both Dna and Rna Virus mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, ZBP1 has been identified as a sensor of IAV vRNPs that triggers PANoptosis ( Figure 2 ) [ 18 ]. During infection, ZBP1 interacts with RIPK3 via the RHIM domain and recruits caspase-8 and the NLRP3 inflammasome sensor to promote assembly of a PANoptosome complex that drives PANoptosis [ 18 , 41 , 42 , 43 ]. The ZBP1-dependent PANoptosome is required for NLRP3– and capsase-1–dependent inflammasome activation, pyroptosis, and maturation of proinflammatory cytokines including IL-1β and IL-18 during IAV infection.…”
Section: Panoptosis In Viral Infectionmentioning
confidence: 99%